Osteonevus of Nanta Presenting as Nodule over Left Eyebrow - Girish Kamat; Aneel Myageri; Ravikala Rao (Hindawi Limited, 2012)
Osteonevus of Nanta is a rare histopathological finding in which there is an ectopic bone formation in intradermal nevus. Very few cases have been reported so far in the literature. We present a case of osteonevus of Nanta, which occurred as a nodule over the left eyebrow in a 52-year-old female patient. Simple excision proved to be curative in the present case.